2020
DOI: 10.5154/r.textual.2020.75.04
|View full text |Cite
|
Sign up to set email alerts
|

La apropiación forestal comunitaria en la Sierra Juárez de Oaxaca ante las políticas forestales

Abstract: C ommunity appropriation of forest resources in the Sierra Juarez of Oaxaca was the result of disputes and various conflicts of interest. This paper describes the process of agrarian communities in the appropriation of forest resource management. The analysis model was based on the following inflection points: the granting of forest concessions, their abrogation driven by the community movement, and local management of forest resources. The proposed analytical models identified the following concepts: utilitar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…Andiphilum that did not correspond to any previously described species. At the collection site, the vegetation corresponds to montane cloud forest, and the climate in the region, approximately between 1,800-2,600 m is temperate subhumid with summer rains (Aquino-Vásquez et al, 2012). The new species is described and illustrated, using fertile, living, and dry material.…”
Section: Methodsmentioning
confidence: 99%
“…Andiphilum that did not correspond to any previously described species. At the collection site, the vegetation corresponds to montane cloud forest, and the climate in the region, approximately between 1,800-2,600 m is temperate subhumid with summer rains (Aquino-Vásquez et al, 2012). The new species is described and illustrated, using fertile, living, and dry material.…”
Section: Methodsmentioning
confidence: 99%
“…The answer is affirmative, since empirically numerous cases have shown that it is feasible to Brazilian Journal of Development, Curitiba, v.9, n.9, p. 25953-25968, sep., 2023 find various initiatives and turn them into large detonating projects for the benefit of peasant families who live in an environment in which everything seems to be against them. As an example, I will cite two cases for the state of Oaxaca, the first refers to the use of forest resources of the communities of the Sierra Juárez (Sastré, 2008;Aquino-Vásquez et al, 2020) where not only has favorably the income of families and their communities but also the environment through a sustainable use of resources. Another example is given in the production of vegetables in greenhouses in communities of the Central Valleys of Oaxaca (Rodríguez et al, 2015), where marginalized small producers have ventured into tomato production in a profitable and competitive manner.…”
Section: Introductionmentioning
confidence: 99%